Alcohol consumption and risk of upper-tract urothelial cancer. (June 2017) - Zaitsu, Masayoshi; Kawachi, Ichiro; Takeuchi, Takumi; Kobayashi, Yasuki
Highlights: The risk of alcohol use in upper tract urothelial cancer (UTUC) is unknown. The risk of UTUC is elevated at 15 g ethanol/day with a dose-response trend. Alcohol consumption is associated with a risk of UTUC. Abstract: Background: Upper-tract urothelial cancer (UTUC), which includes renal pelvic cancer and ureter cancer, is a rare cancer and its prognosis is poor. Smoking and high-risk occupations (e.g., printing and dyestuff working which involves exposure to aniline dyes) are well-known risk factors for UTUC. However, the risk of alcohol consumption in UTUC remains unclear. This study aimed to determine whether alcohol consumption is an independent risk factor for UTUC. Methods: The study was a case–control study which used the nationwide clinical inpatient database of the Rosai Hospital group in Japan. We identified 1569 cases and 506, 797 controls between 1984 and 2014. We estimated the odds ratio (OR) and 95% confidence interval (95%CI) of alcohol consumption for UTUC – never, up to 15 g/day, >15–30 g/day, or >30 g/day – using unconditional logistic regression. We adjusted for the following covariates: age, sex, study period, hospital, history of smoking, and high-risk occupation. Results: The risk of UTUC was significantly higher in ever-drinkers compared with never-drinkers (OR = 1.23, 95%CI, 1.08–1.40; P = 0.001). Compared with never-drinkers, the risk threshold for UTUC was >15 g of alcohol consumption per day (equivalent to 6 ounces of Japanese sake containing 23 g of alcohol). A dose-response was observed ( P < 0.001). Conclusion: Alcohol consumption may be an independent risk factor for UTUC, with a low-risk threshold of 15 g of alcohol per day.